2015
DOI: 10.1089/jir.2014.0031
|View full text |Cite
|
Sign up to set email alerts
|

Laparotomy in Mice Induces Blood Cell Expression of Inflammatory and Stress Genes

Abstract: Surgical trauma induces immune and stress responses although its effects on postsurgical inflammatory and stress gene expression remain poorly characterized. This study sought to improve current scientific knowledge by investigating the effects of laparotomy on mouse blood cell inflammatory and stress gene expression. Threemonth-old male C57BL/6J mice were subjected to 2% isoflurane or 2% isoflurane with laparotomy and sacrificed 4 h postintervention. Blood was collected and blood cell expression of 158 genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Our study also supports previous research demonstrating that surgery is associated with an increased inflammatory response. 22 We observed that the levels of most inflammatory cytokines were higher on day 6 than day 1 postoperatively. Although a late peak in cytokines is certainly possible, we cannot rule out that we might have missed the peak levels of some cytokines, which might have occurred on postoperative day 2 or 3.…”
Section: Discussionmentioning
confidence: 66%
“…Our study also supports previous research demonstrating that surgery is associated with an increased inflammatory response. 22 We observed that the levels of most inflammatory cytokines were higher on day 6 than day 1 postoperatively. Although a late peak in cytokines is certainly possible, we cannot rule out that we might have missed the peak levels of some cytokines, which might have occurred on postoperative day 2 or 3.…”
Section: Discussionmentioning
confidence: 66%
“…As a first step to better understand this biology, we previously modeled surgical trauma introduced via laparotomy in 3-month-old male C57BL/6J mice and showed that this procedure induces coordinated, post-operative blood cell expression of unique inflammatory and oxidative or metabolic stress genes. [14] Moreover, in a model of postoperative stress in adult rats, changes in lipid mediators (LMs) that modulate inflammation in intestinal mucosa after laparotomy were previously observed. [15] In the current study, we sought to further characterize the effects of laparotomy on post-operative physical function, skeletal muscle gene expression and LM levels in C57BL/6N mice across the life span (3,20 or 24 months of age) in order to investigate the impact of age and function on late-life vulnerability and resiliency to acute surgical stress.…”
Section: Introductionmentioning
confidence: 99%